2020
DOI: 10.1111/jsr.13229
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and non‐pharmacological interventions to enhance sleep in mild cognitive impairment and mild Alzheimer's disease: A systematic review

Abstract: Suboptimal sleep causes cognitive decline and probably accelerates Alzheimer's Disease (AD) progression. Several sleep interventions have been tested in established AD dementia cases. However early intervention is needed in the course of AD at Mild Cognitive Impairment (MCI) or mild dementia stages to help prevent decline and maintain good quality of life. This systematic review aims to summarize evidence on sleep interventions in MCI and mild AD dementia. Seven databases were systematically searched for inter… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 69 publications
0
39
0
1
Order By: Relevance
“…Neurodegeneration is accompanied by sleep difficulties due to reduction of amplitude and phase changes of circadian rhythms such as that of melatonin secretion, as well as the disturbing influences of neurodegenerative processes on sleep. The relation between sleep and neurodegenerative diseases is bidirectional and several studies have shown that sleep disruption is a major contributor to neuropathology ( 30 , 73 76 ). Alzheimer disease (AD) patients with disturbed sleep-wake rhythms did not only exhibit reduced amounts of melatonin secretions, but also a higher degree of irregularities in the melatonin pattern, such as variations in phasing of the peak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurodegeneration is accompanied by sleep difficulties due to reduction of amplitude and phase changes of circadian rhythms such as that of melatonin secretion, as well as the disturbing influences of neurodegenerative processes on sleep. The relation between sleep and neurodegenerative diseases is bidirectional and several studies have shown that sleep disruption is a major contributor to neuropathology ( 30 , 73 76 ). Alzheimer disease (AD) patients with disturbed sleep-wake rhythms did not only exhibit reduced amounts of melatonin secretions, but also a higher degree of irregularities in the melatonin pattern, such as variations in phasing of the peak.…”
Section: Resultsmentioning
confidence: 99%
“…An emerging symptom of this circadian disruption is “sundowning,” a chronobiological phenomenon observed in patients with AD along with sleep and wakefulness disorder. “Sundowning” is characterized by symptoms appearing in the late afternoon or early evening, which include reduced ability to maintain attention to external stimuli, disorganized speech, and thinking, a variety of motor disturbances including agitation, wandering, and repetitious physical behaviors with emotional disturbances ( 30 , 73 76 ).…”
Section: Resultsmentioning
confidence: 99%
“…Beyond pharmacological treatments, several non-invasive techniques have recently demonstrated their ability to modulate the human EEG oscillations during sleep with beneficial effects on memory [173,174]. Therefore, the interest in their possible application in healthy and pathological aging is progressively growing [175][176][177], and several encouraging results are available (Table 2). This approach fits with the general notion that monitoring and managing sleep EEG features may support brain plasticity-dependent process during rehabilitative paradigms in different pathological conditions [178].…”
Section: Innovative Nrem Sleep-based Techniques For Prevention and Care Of Alzheimer's Diseasementioning
confidence: 99%
“…One recent review summarized the effects of several sleep interventions that have been studied in patients with MCI or mild dementia, including Cognitive Behavioral Therapy-Insomnia (CBT-I), a structured limbs exercise program, aromatherapy, phase locked loop acoustic stimulation, transcranial stimulation, suvorexant, melatonin, donepezil, galantamine, rivastigmine, tetrahydroaminoacridine, and Continuous Positive Airway Pressure (CPAP) and concluded that CBT-I, melatonin, suvorexant, and CPAP for OSA hold the most promises. [ 25 ] Since medications might further impair cognition, non-pharmacological interventions are of particular interest for older adults who are at high risk for dementia. Cordone et al [ 26 ] highlighted several promising techniques to enhance NREM sleep oscillations that have solid scientific basis for preventing or slowing down AD pathology but remain to be tested in clinical settings.…”
Section: Recent Progress In the Research Of Admentioning
confidence: 99%